Effect of Chitosan Extracted from Vannamei Shrimp (Litopenaeus vannamei) Shells in Feed on the Growth Performance and Digestibility of Nile Tilapia (Oreochromis niloticus) - Rangkuti, Putra; Suharman, Indra; Siagian, Desi Rahmadani (Jurnal Natur Indonesia, 2025)
Chitosan extracted from vannamei shrimp shells has the potential to act as an attractant for Nile tilapia (Oreochromis niloticus) while also enhancing growth performance and digestibility in various fish species. This study evaluated the impact of chitosan supplementation in feed on Tilapia's growth rate and digestibility. The experiment was designed using a Completely Randomized Design (CRD) with five treatment groups and three replications. Fish were fed diets containing chitosan at 0%, 1%, 2%, 3%, and 4% for 56 days. 525 tilapia fingerlings (2.50±0.41 g) were stocked in 15 floating net cages (1x1x1 m3). Feed was provided at 10% of the fish biomass three times daily at 08:00 AM, 01:00 PM, and 05:00 PM. The results indicated that chitosan supplementation significantly (P<0.05) influenced Tilapia's specific growth rate and digestibility. Among the tested levels, the 4% chitosan treatment yielded the highest values, including overall digestibility (52.38%), protein digestibility (74.72%), protein retention (27.27%), feed efficiency (34.77%), specific growth rate (3.33%), and 100% survival rate. These findings suggest that incorporating chitosan into tilapia feed can enhance growth performance and nutrient utilization.